Palladium-Catalyzed Carbonylation of Coumarin C(sp2)–H Bonds: A New Entry to Arylcoumarin Ketones - Mirzaei, Siyavash; Rajai-Daryasarei, Saideh; Soheilizad, Mehdi; Kabiri, Roya; Ansari, Samira; Shabanian, Meisam; Pashazadeh, Rahim (Synthesis, 2019)
A facile and efficient palladium-catalyzed carbonylation of coumarins involving two C–C bond formations has been developed. The C–H bond oxidative functionalization proceeds through aroylation with insertion of carbon monoxide to give arylcoumarin ketones. The reaction conditions, employing ambient pressures of CO gas as C1 feedstock, dramatically improve the generality of the carbonylation of aryl halides.
Keywords: Pd catalysis; carbonylation; arylcoumarin ketones; aryl halides; carbon monoxide.